2012
DOI: 10.1038/leu.2012.215
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive CD14+HLA-DRlow/neg IDO+ myeloid cells in patients following allogeneic hematopoietic stem cell transplantation

Abstract: Myeloid-derived suppressor cells (MDSCs) have emerged as a heterogeneic immunoregulatory population that can expand in response to inflammatory signals. Predominantly studied in cancer, MDSCs suppress T cells utilizing various mechanisms. In allogeneic hematopoietic stem cell transplantation (allo-HSCT) therapy-related toxicity and alloreactivity increase inflammatory cytokines that might favor an MDSC accumulation. To address this question, circulating CD14 þ HLA-DR low/neg cells were studied retrospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
117
2
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(131 citation statements)
references
References 53 publications
10
117
2
2
Order By: Relevance
“…We failed to find an association between IDO activity and vitamin D levels. This might be because IDO activity in serum by circulating monocytes 26 overshadows DC activity in the tissues, but more studies focusing on vitamin D effects in vivo are needed. Previous studies have shown conflicting results; although one study on 53 adult patients suggests an association between vitamin D levels and cGvHD incidence, 6 others have reported better outcomes in established cGvHD after vitamin D supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…We failed to find an association between IDO activity and vitamin D levels. This might be because IDO activity in serum by circulating monocytes 26 overshadows DC activity in the tissues, but more studies focusing on vitamin D effects in vivo are needed. Previous studies have shown conflicting results; although one study on 53 adult patients suggests an association between vitamin D levels and cGvHD incidence, 6 others have reported better outcomes in established cGvHD after vitamin D supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies are required to incorporate data on myeloid populations in such global profiling of immune reconstitution. 47 In summary, multivariate methods such as correspondence analysis and unsupervized clustering provide useful tools to analyze immune reconstitution and point to the crucial role of CMV serostatus (and CMV replication), and chronic GvHD in shaping long-term immune reconstitution following allogeneic hematopoietic stem cell transplantation. Application of such tools to independent cohorts with different flow cytometry panels may help validate this approach and gain novel insights into immune recovery.…”
Section: Discussionmentioning
confidence: 99%
“…1) and expressed CD163. Of note, CD163 is a marker indicative of M2 polarization that is also present on monocytic IDO + MDSC in patients suffering from graft-versus-host disease after allogenic hematopoetic stem cell transplantation (data not shown) (20). This effect was not observed when CD14 + monocytes were cocultured with the hepatoma cell line HUH7 (data not shown).…”
Section: Purified Catalase Induced Functional Mdsc From Peripheral Blmentioning
confidence: 95%
“…Images were acquired using a Zeiss-Axiovert microscope (Zeiss, Jena, Germany). qPCR qPCR for cytokines/enzymes associated with MDSC immunosuppression (such as arginase and IL-10) and for analysis of oxidative stress (NADPHoxidase subunits) was performed as described previously (20). Total RNA was extracted from purified monocytes and CD14 + HLA-DR low/2 cells ex vivo and after coculture with purified catalase using the RNeasy mini kit (Qiagen, Hilden, Germany) and purity determined spectroscopically.…”
Section: May-gr€ Unwald-giemsa Staining Of Monocyte Cytospinsmentioning
confidence: 99%
See 1 more Smart Citation